2019
DOI: 10.1021/acs.molpharmaceut.9b00719
|View full text |Cite
|
Sign up to set email alerts
|

2D NMR Analysis of the Effect of Asparagine Deamidation Versus Methionine Oxidation on the Structure, Stability, Aggregation, and Function of a Therapeutic Protein

Abstract: Two of the most common forms of chemical modifications that compromise the efficacy of therapeutic proteins are the deamidation of asparagine residues and oxidation of methionine residues. We probed how deamidation affects the structure, stability, aggregation, and function of interferon alpha-2a (IFNA2a), and compared with our earlier results on methionine oxidation. Upon deamidation, no significant changes were observed in the global secondary structure of IFNA2a with minor changes in its tertiary structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…The percentages of correct forms varied between different manufacturers, and relatively stable between different batches, demonstrating the status of disulfide bonds were related to expression procedure. Oxidation of Met residues and deamidation of Asp residues are two of the most common forms of chemical modifications that compromise the efficacy of therapeutic proteins [21]. In intact protein analysis, oxidized IFNα2b was only found in sample 4E (24.2%) and 6P (14.7%), but in peptide mapping, oxidized peptides were found in all seven samples, suggesting that oxidation could happen during sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of correct forms varied between different manufacturers, and relatively stable between different batches, demonstrating the status of disulfide bonds were related to expression procedure. Oxidation of Met residues and deamidation of Asp residues are two of the most common forms of chemical modifications that compromise the efficacy of therapeutic proteins [21]. In intact protein analysis, oxidized IFNα2b was only found in sample 4E (24.2%) and 6P (14.7%), but in peptide mapping, oxidized peptides were found in all seven samples, suggesting that oxidation could happen during sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…As most proteins are amphiphilic and surface active, they have a tendency towards adsorption at the ALI. Upon adsorption, conformation changes may occur, exposing hydrophobic residues to the interface to avoid contact with water, thus leading to aggregation and unfolding, which are the main factors contributing to protein instability [ 67 , 68 ]. Chemical degradation of proteins (deamidation, oxidation, glycation) may also cause aggregation (either covalent or non-covalent) [ 67 ].…”
Section: Challenges and Considerations In The Development Of Protein mentioning
confidence: 99%
“…These findings revealed that deamidation destabilised IFNA2a and enhanced its tendency to aggregate under stressful conditions, and reduced its function to a greater extent than oxidation. This is the first study that quantitatively compared the effects between deamidation and oxidation of a therapeutic protein [ 68 ]. It would be a good strategy to conduct such studies early on in the development of therapeutic protein candidates in order to identify the chemical modifications that a particular protein would be susceptible to, and to test out various excipients that could resolve specific stability issues.…”
Section: Challenges and Considerations In The Development Of Protein mentioning
confidence: 99%
See 2 more Smart Citations